Progressive failure behavior and stress evolution characteristics of fractured coal-rock combination structure - Kai WANG; Xiang ZHANG; Feng DU; Yang JU; Kangnan LI; Jiazhi SUN; Yiqiao WANG; Xiaohuan ZUO (Meitan xuebao)
The structural weak planes have a significant impact on the mechanical properties of rock (coal) masses. Under the influence of geological structures or mining activities, the surrounding rock in deep mines commonly exhibits a coal-rock combination structure containing macroscopic fractures. Therefore, studying the mechanical properties of fractured coal-rock combination samples is of great importance for the control of surrounding rocks in deep tunnels and for the prevention and mitigation of dynamic coal and rock disasters. The study conducts a comparative analysis of the effects of different fracture positions and fracture angles on the evolution of the mechanical properties and the progressive failure characteristics of fractured coal-rock combination samples. Furthermore, a discrete element model of the fractured coal-rock combination structure was established to investigate the evolution of the stress field, as well as the dynamic relationship between crack initiation and propagation and the characteristic stress values under varying fracture positions and angles. Finally, based on the theory of stress fields at fracture tips and interface constraint effects, the mechanical mechanism of the fractured combination structure under uniaxial compression were discussed. The results indicate that fractures primarily affect the coal mass within the structure, leading to a significant reduction in both strength and deformation capacity of the coal-rock combination structure samples. As the fracture angle increases, crack closure stress, yield stress, peak stress, initial deformation modulus, and elastic modulus of the samples all show an exponential increase. The presence of interface fractures causes earlier initiation of damage in the combination structure samples, and during the yield stage, the acoustic emission count occupies a relatively high proportion throughout the entire loading process. When the fracture angle is close to horizontal, the cracks in the samples propagate rapidly before reaching peak stress, and the cumulative damage degree is greater. The strain localization zones in different samples tend to propagate inward into the coal mass, ultimately leading to the formation of macroscopic tensile cracks either within the individual materials or across the interface. The study also identified the characteristic regional distributions of force chain fields and stress fields, revealing that changes in the fracture angle can cause a deflection of these characteristic regions, which significantly influences the interface constraint effect. The presence of fractures significantly alters the distribution of the ultimate strength of the coal and rock components within the conventional coal-rock combination structure.